2014
DOI: 10.1108/bfj-04-2013-0098
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the organic potential of urban Indian consumers

Abstract: Purpose – The purpose of this paper is to explore the potential for the purchase of organic food products amongst urban Indian consumers. Design/methodology/approach – The paper is based on a sample of 618 urban Indian consumers. The study questionnaire was developed to measure food-related lifestyle and attitudinal variables. The respondents were also questioned regarding their grocery purchase behaviour; awareness and purchase intentio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 39 publications
1
16
1
3
Order By: Relevance
“…These perceptions may be toward stakeholders involved in the supply chain as well as certification agencies. The findings are contrary to the existing literature that indicated lack of trust of stakeholders (Chen et al, 2014;Scalvedi & Saba, 2018) and certification agencies (Pham et al, 2018;Sondhi, 2014) as the constraint impeding organic food consumption. The possible reasoning explaining inconsistent results could be that introduction of alternative buying possibilities such as farmers markets, community-supported agriculture, and grow your own food networks.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…These perceptions may be toward stakeholders involved in the supply chain as well as certification agencies. The findings are contrary to the existing literature that indicated lack of trust of stakeholders (Chen et al, 2014;Scalvedi & Saba, 2018) and certification agencies (Pham et al, 2018;Sondhi, 2014) as the constraint impeding organic food consumption. The possible reasoning explaining inconsistent results could be that introduction of alternative buying possibilities such as farmers markets, community-supported agriculture, and grow your own food networks.…”
Section: Discussioncontrasting
confidence: 99%
“…Misra and Singh (2016) suggested that doubt in regard to the professed quality of organic food hinders organic food consumption. On the contrary, this findings supports the existing literature which conclude that healthiness (Botonaki et al, 2006;Bryła, 2016;Cerjak et al, 2010;Hasimu et al, 2017;Henryks et al, 2014;Janssen, 2018a;Lea & Worsley, 2005;Lillywhite et al, 2013a;Misra & Singh, 2016;Nandi et al, 2016;Petrescu et al, 2017;Scalvedi & Saba, 2018;Sobhanifard, 2018;Sondhi, 2014;Thøgersen et al, 2015b;Thøgersen & Zhou, 2012;von Meyer-Höfer et al, 2015;Zagata, 2014), natural ingredients (Hasselbach & Roosen, 2015a;Janssen, 2018b;Sobhanifard, 2018;Thøgersen & Zhou, 2012;Zagata, 2014) and free from characteristics (González, 2009;Henryks et al, 2014;Nandi et al, 2017;Zagata, 2014) acts as the positive influencer for buying organic food.…”
Section: Discussionsupporting
confidence: 86%
“…But the past 2-3 years have seen a significant increase in the published literature in the area of organic food purchase preferences and behavior (Balaji & Injodey, 2017;Misra & Singh, 2016;Prakash, Singh, & Yadav, 2018;Sondhi, 2014;Yadav, 2016;Yadav & Pathak, 2016) in the Indian context. However, these studies were quantitative using close-ended questions that may limit the respondents to express their motivations/barriers of using organic food products (Kim, Eves, & Scarles, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Though extensive studies have been conducted across the world, there is a serious lack of similar data with regards the Indian context. Most of the existing studies have looked more at potential consumers (Sondhi, 2014) rather than existing consumers.…”
Section: Scope and Objectives Of The Studymentioning
confidence: 99%
“…Most consumer studies that are available have looked at potential health conscious consumers (Sondhi, 2014) or looked at organic purchase intentions amongst general public (Shafi and Madhavaiah, 2013). Sondhi and Vani (2007) assessed the market potential from the supplier side by conducting a retailer study to assess the current status and future prospect of the organic market in the Indian context.…”
Section: Organic Food Consumption: An Emerging Market Opportunity?mentioning
confidence: 99%